Ko umetna inteligenca prevzame razvoj internih orodij - Kovač, Gregor; Kozlar, Tomaž; Žvokelj, Žan (OTS 2026 Sodobne informacijske tehnologije in storitve: Zbornik 29. konference, 2026)
In last year's article, we presented our own low-code platform for ERP system development, built on SQL and a Java core, with the tools FormTool and Linea. This year, we are checking whether artificial intelligence can become a real help in the development and maintenance of our internal tools. We first look for the answer in the example of QueryTool, which we use the agent programming tool to rewrite from the existing environment to the Laravel web platform. Artificial intelligence has also helped us with other internal tools, such as monitoring, server deployment, user support, and the like. We place the experience in a broader, engineering and ethical framework and highlight where the help of artificial intelligence was productive and where the developer retained the leading role.